Changing Admission Patterns in Pediatric Emergency Departments during the COVID-19 Pandemic in Italy Were Due to Reductions in Inappropriate Accesses - Ivana Rabbone; Francesco Tagliaferri; Elena Carboni; Beatrice Crotti; Jessica Ruggiero; Alice Monzani; Lorenza Bonetti; Martina Soliani; Simonetta Bellone; Claudio Cavalli; Andrea E. Scaramuzza (MDPI AG, 2021)
During the initial phase of the national lockdown, we found that there were sharp decreases in admissions to two pediatric emergency departments (EDs) in northern Italy (Cremona and Novara). Here we present a detailed analysis of these admission patterns and types of admissions over a longer timeframe. ED admissions data were anonymously extracted from the departmental management software. Admissions data from 2019 and 2020 were analyzed and compared separately for each ED and combined. There was a 73.2% decrease in total admissions compared with the same period in 2019. With respect to admission diagnoses, there was a significant (p < 0.001) drop in infectious (−51%), respiratory (−25.5%), and nervous systems diseases (−50%) and injuries and poisoning (−17%) but not endocrine, metabolic, neoplastic, circulatory, or musculoskeletal diseases. White codes (patients with minor injuries for whom ED medical care is not required) significantly decreased by 56.3% (p < 0.001). Even if the COVID-19 pandemic represented an enormous healthcare burden in Italy, especially during the first months of the pandemic (late February to May), the workload of pediatric EDs was significantly reduced, especially for unnecessary accesses (white codes).